Peran Sistem Informasi Manajemen Bank Syariah Indonesia Dalam Membantu Peningkatan Perekonomian Dan Bisnis di Era Digital - Soleha, Safnah; Sibuea, Parulian; yunanda, Mey; Harahap, Indah Tri Sari; Nasution, Alya Arianti (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The purpose of this research is to find out the role of the management information system of Indonesian Islamic banks in helping to improve the economy and business in the digital era, Bank Syariah Indonesia is encouraged to be able to compete at the global level in national economic development and contribute to the welfare of society, with a modern and universal concept. The type of research used in this paper is to use literature studies obtained from several sources. The results of the study The role of sharia banks in economic progress is that sharia banking in its operations emphasizes controlling the level of productivity according to financing including mudharabah and musyarakah. BSI's support and services for SMEs give entrepreneurs the opportunity to expand their business without having to use online loans or other high-interest loans that can exacerbate problems during a prolonged business crisis. The role of Management Information Systems in Islamic banking is significant in supporting the goal of a more inclusive and equitable economy